Self Love Pada Remaja SMA - Anissa Khumairoh; Nafisah Charisma; Azzahra Anggun; Annisa Siti Solikah Satradanie; Aqvina Rahma Diyanti; Sidney Tsany Chavvah Abenza (Pusat Riset dan Inovasi Nasional, 2024)
In the era of digitalization like this, and in the realm of the process of finding the identity of a teenager, it is very easy for teenagers to be affected by many good and bad things by the surrounding environment. The problem that is often faced by teenagers is mental health where there are many causes and consequences that can trigger this to happen. Because of this problem, teenagers lack an understanding of self-love or love themselves. Self love has the meaning of a feeling where we feel confident and proud of our own abilities without attaching importance to the opinions of others by involving aspects of self-awareness, self-confidence, and caring for ourselves. Looking at the reality, this article uses qualitative methods and literature studies in answering these problems. In the interview that we have conducted to 7 existing resource persons and contain active high school teenagers based in the city of Surakarta. With the hope that the interview that has been done can help some and even all speakers about the importance of 'self love' for themselves. With the results we get in several existing aspects such as self awareness, self care, self esteem and in the 7th self worth aspect, the informant has a fairly good and high percentage. Even though in the aspect of self esteem at the same time it is still wrapped in a sense of insecurity.